Waste Material Adsorbents for Zinc Removal from Wastewater: A Comprehensive Review - Haider M. Zwain; Mohammadtaghi Vakili; Irvan Dahlan (International Journal of Chemical Engineering)
This review examines a variety of adsorbents and discusses mechanisms, modification methods, recovery and regeneration, and commercial applications. A summary of available researches has been composed by a wide range of potentially low-cost modified adsorbents including activated carbon, natural source adsorbents (clay, bentonite, zeolite, etc.), biosorbents (black gram husk, sugar-beet pectin gels, citrus peels, banana and orange peels, carrot residues, cassava waste, algae, algal, marine green macroalgae, etc.), and byproduct adsorbents (sawdust, lignin, rice husk, rice husk ash, coal fly ash, etc.). From the literature survey, different adsorbents were compared in terms of Zn2+ adsorption capacity; also Zn2+ adsorption capacity was compared with other metals adsorption. Thus, some of the highest adsorption capacities reported for Zn2+ are 168 mg/g powdered waste sludge, 128.8 mg/g dried marine green macroalgae, 73.2 mg/g lignin, 55.82 mg/g cassava waste, and 52.91 mg/g bentonite. Furthermore, modification of adsorbents can improve adsorption capacity. Regeneration cost is important, but if consumption of virgin adsorbent is reduced, then multiple economic, industrial, and environmental benefits can be gained. Finally, the main drawback of the already published Zn2+ adsorption researches is that their use is still in the laboratory stage mostly without scale-up, pilot studies, or commercialization.